(untitled) (The Journal of Psychology and Sociology, 2025)
The study extends the scope of understanding of the religious/spiritual landscape of Kazakhstani society, which is subject to significant changes caused by macro and micro contextual factors and the growth of new religious/spiritual forms of believe. It aims to assess the complex and straightforwardness of the religious consciousness of Kazakhstani youth, its key role in changing traditional religious practices and attitudes, and attempts to adapt them to modern realities and challenges. The departure of young people from traditional models of organised religiosity and the search for mystical experience and other alternative forms of religiosity/spirituality, manifested in the growing interest in Eastern religious teachings and personal spiritual practices, actualises the research and practical significance. This article presents a sociological analysis of the religious and spiritual attitudes of Kazakhstani youth based on two waves of data collected through quantitative surveys (December 2023 – March 2024) among youth aged 18-35. The sample size is 2000 respondents, with regional quotas based on age and gender applied. Professional 3KA software (licence E-B-9979) facilitated qualitative data collection. IBM SPSS Statistics version 30.0.0.0.0 (172) was used to analyse the quantitative data. The study used modern sociological tools to measure Kazakhstani youth’s religiosity/spirituality, identity and well-being. An adapted version of the Five Dimensions of Religiosity questionnaire (Pearce et al., 2017) was used to measure indicators of religiosity, and the Bogardus scale and Cronbach’s alpha coefficient were used to measure social distance, providing a statistical measure of reliability and internal consistency. The data were analysed using descriptive statistics, contingency tables, chi-square (χ²), correlation analysis, and the Mann-Whitney U test for independent samples. The study’s results demonstrate different patterns of Kazakhstani youth’s perception of religious/non-religious and spiritual beliefs. Keywords: religiosity, spirituality, youth, hijab, spiritual practices, religious identity, faith, belief.